The effect of Megasphaera elsdenii, a probiotic, on the productivity and health of Holstein cows - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2008.